Epidemiology of anorexia nervosa. Prevalence of anorexia nervosa in female adolescents from the districts of Lisboa and Setubal. - Do Carmo, I; Reis, D; Varandas, P; Bouça, D; Santo, D P; Neves, A; André, I; Sampaio, D; Galvão-Teles, A (Acta Médica Portuguesa, 2001)
Prevalence studies of anorexia nervosa (AN) have shown differences depending of the country and method applied. The partial syndrome is being emphasized. There has been no epidemiological study done on AN in the Portuguese population of continental Portugal. Our objectives were: 1) to study the prevalence of AN in Portuguese populations; 2) to study the presence of partial syndrome and of body image disturbance; 3) to calculate the number of girls dieting; 4) to correlate with other variables. A population of 2,398 girls ranging 10 to 21 years old, from 30 State secondary schools in the Lisbon and Setubal districts were studied. A questionnaire was answered with questions allowing assessment of all DSM IIIR criteria for AN. RESULTS: Prevalence of AN–0.37%, partial syndrome–12.6%, body image disturbance without weight loss–7%, wish to decrease weight in normal or low weight girls–38%, overweight–15.3%, the peak of age for AN was 15 years, the most prevalent socio-economic class for AN was 2 (scale 1 (higher) to 5). School performance was worse with AN and the age menarche was sooner.